2021
DOI: 10.5559/di.30.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Instructional Quality during the COVID-19 Pandemic: A Moderated Mediation Analy

Abstract: The school lockdown caused by the COVID-19 pandemic pushed teachers to online teaching literally overnight, which put their performance at risk. Transformational school leadership (TSL), teacher self-efficacy (TSE) and digital competencies might have played a protective role in such burdening conditions. Therefore, the present study aimed to examine the mediating role of TSE in explaining the relationship between TSL and instructional quality. Additionally, the moderating role of digital competencies in explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The effect of school leadership on the mediator variable, teacher agency, was greater when the power distance in principal-teacher relations was less pronounced. Teaching quality was also measured as a dependent variable in a study conducted in Croatia by Burić et al. (2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of school leadership on the mediator variable, teacher agency, was greater when the power distance in principal-teacher relations was less pronounced. Teaching quality was also measured as a dependent variable in a study conducted in Croatia by Burić et al. (2021).…”
Section: Resultsmentioning
confidence: 99%
“…(2021). Burić et al. (2021) reported that transformational leadership had a direct and indirect effect on different dimensions of teaching quality during the Covid-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also state that collaboration can be enhanced by organizing distinct employee interests with joint interests (Sayyadi and Provitera, 2021). This is suitable for leaders in any organization including business, hospitality (Elkhwesky et al, 2022) or education (Burić et al, 2021). Thus, an organization must focus on three key components of skills and abilities for post-covid recovery.…”
Section: Findings and Analysismentioning
confidence: 99%